Studi Komparatif (Comparative Constitutional Law) Antara Negara Demokrasi dan Negara Islam di Tinjau dari Persfektif Politik dan Keadilan - Afrinald Rizhan (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan ilmu Politik Universitas Riau Kep, 2017)
Abstract The law is always identified with justice, because the law must reflect justice and at the same time maintain justice. Law as a moral category is similar to justice. The word